Gelatinous Carbon Impacts Benthic Megafaunal Communities in a Continental Margin - Lebrato, Mario; Molinero, Juan-Carlos; Mychek-Londer, Justin G.; Gonzalez, Elena Mateo; Jones, Daniel O. B. (Frontiers in Marine Science, 2022)
Post-collapse of seasonal blooms of gelatinous zooplankton (Cnidaria, Ctenophora, and Thaliacea) sinking carcasses transports labile carbon (jelly-C) to benthic continental margins and the deep sea. In recent decades, bloom frequency and intensity have increased globally; however, how sinking jelly-C affects benthic communities is poorly known. Further, as climate change and other anthropogenic impacts may increase gelatinous blooms in the future, understanding the contributions and impacts of jelly-C upon benthic communities is of pivotal importance. Thus, in this study, we assessed jelly-C deposits post-intense blooming of a pelagic species of marine colonial gelatinous tunicate in the Thaliacean class, Pyrosoma atlanticum. We studied the seabed using a remotely operated vehicle (ROV) from 26 to 1,276 m, documenting jelly-C deposits and species of the megafaunal benthic community. Environmental variables from water column profiles at transects near our own off the Ivory Coast of West Africa were used in assessments. Jelly-C biomass peaked at 400 m (1,500 grC 100 m−2) and remained at the average (300 grC 100 m−2) through 1,276 m. Typically, in depth strata between 300 and 800 m, peaks in jelly-C biomass (500 to 1,500 grC 100 m−2) corresponded to areas with significantly reduced benthic megafaunal species abundances as well as diversity. From 800 to 1,276 m, we noted patchier jelly-C biomass deposits where individual megafauna species abundances and diversity correspondingly increased, yet total organism counts remained low. We observed 11 species from 5 phyla directly feeding on jelly-C and 10 single-species aggregations triggering megafaunal dominance events at various localized depth strata. Although such dynamics have been hypothesized and examined for some time with respect to phytodetritus biomass, they have been rarely described for jelly-C. Thus, our novel findings for jelly-C dynamics in the offshore regions can help to provide a better understanding of the ecological role that this component plays in marine benthic ecosystems and continental margins.